Gender Leadership Imbalance in Academia: An Etiological Approach - Krambia-Kapardis, Maria; Mavrikiou, Petroula; Symeou, Loizos (My University, 2025)
Whilst there has been an increasing trend of women holding academic positions in European Higher Tertiary Institutions (HTIs), leadership positions are held predominantly by men. The study draws on radical feminism theory with which its methodology is aligned by investigating the perceptions of both genders. To that end, the study categorizes the impediments holding women back from breaking the glass ceiling into endogenous and exogenous factors. By doing so, the authors are in a better position to recommend the implementation of policies and procedures to address this inequality and navigate towards achieving sustainable gender equality. The research was conducted using an online survey questionnaire administered among all academic and administrative staff of universities in the Republic of Cyprus, the country with the highest glass ceiling in the EU. The authors found that the binary genders differ in their perceptions of what keeps women from breaking the glass ceiling and that this is attributable to exogenous factors, namely, (a) the walls created by male leaders, reinforcing a feeling of marginalization and mansplaining; and (b) family obligations enhancing women’s experiencing a lack of time and burnout. Furthermore, the exogenous factors and the extremely gendered higher echelons of HTIs underpin the endogenous factor of self-sabotage, making women feel they would rather avoid the toxic leadership environment with its lack of professional credit, a view supported by radical feminism theory. The authors suggest practical policy implications to rectify the gender imbalance in leadership in HTIs and suggest directions for future research.
Keywords: higher tertiary institutions; gendered leadership; radical feminism; glass ceiling; academia